ANALISIS KUALITAS LAYANAN AKADEMIK PROGRAM STUDI PENDIDIKAN TEKNIK MESIN UNS DENGAN METODE SERVQUAL DAN QFD (QUALITY FUNCTION DEPLOYMENT) - Kostiyah Dewi Arini; Budi Harjanto; Indah Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2023)
This study aims to (1) analyze the gap between students' perceptions and expectations of the academic services of the Mechanical Engineering Education Study Program, (2) analyze the attributes of academic services that are priorities, and (3) identify improvement efforts that need to be prioritized in order to improve the quality of academic services at Mechanical Engineering Education Study Program. This research is quantitative descriptive. Sources of data in this study is primary data obtained directly from students through questionnaires, and interviews as supporting data. The sampling technique is done by probability sampling. Data collection was done by questionnaire and supported by interviews. The validity test technique used is the Pearson product moment correlation. Data analysis using ServQual and QFD methods. The results of this study are as follows. First, the gap between students' perceptions and expectations of academic services for the Mechanical Engineering Education Study Program obtained a negative servqual score with a total servQual score of -0.45. This means that the quality of services provided by the Study Program has not been able to meet student expectations. Second, service attributes that have the highest normalization and need to be prioritized to be improved according to the needs and expectations of students of the Mechanical Engineering Education Study Program are attributes X3, X11, X10, X32 and X33. Third, improvement efforts that need to be prioritized to improve service quality are based on a range of ratings from 1-10 on technical responses, namely, with the highest score of first rank of 0.05069 found in four technical responses on TR1, TR2, TR3, TR4, TR15, TR16, TR11, TR12, TR13, TR14, TR19, TR20, TR21. The Study Program continues to develop and improve the performance of the academic service quality attributes that are considered important by students and affect student satisfaction.